School based continuous professional development practices at a selected general secondary and preparatory school in Bahir Dar town - Dereje Taye Wondem (Bahir Dar Journal of Education)
Since 2004 School based Continuous Professional Development (CPD) has been implemented in Ethiopian schools with the aim of improving the classroom practices of teachers and consequently improving the achievement of students. However, different reports have revealed that CPD in these schools is not achieving its intended purposes. This necessitates the need to reflect on the CPD practices in our schools so far vis-à-vis the review of the literature on what constitutes successful school based CPD so as to draw lessons for improvement. This study is an attempt to analyze the CPD practices of a selected Secondary and Preparatory school found in Bahir Dar city in light of this review. The study employed a qualitative methodology guided by the interpretive paradigm. Two groups of teachers, the school principal, the cluster supervisor and the school CPD facilitator were purposely selected as sources of data for the study. Interview, focus group discussion and document analysis were used as data gathering tools. Data were analyzed thematically. The analyses of the data revealed that the CPD practices at the selected General Secondary and Preparatory school do not have the basic features of successful teacher professional development programs. Though the administrative structure to run the CPD program is set at school level, the school context is not supportive enough to run the program; the CPD program is not strongly linked with the school improvement program and students’ achievement; and it is not engaging the teachers. So, serious consideration should be given mainly to the capacity development of all the actors involved in the delivery of the program